Upper-body neuromechanical coordination strategies during fatiguing sustained dead hangs in climbers - Exel, J.; Kaufmann, P.; Froschauer, O.; Baca, A.; Kainz, H.; Mochizuki, L. (European Journal of Sport Science, 2026)
ABSTRACT This study investigated how upper-body joint and muscle coordination strategies are related and adapted under fatigue during sustained dead hangs, a task relevant to climbing performance. Eleven climbers performed a dead hang until failure. Joint coordination variability (rCV) was assessed using a modified vector coding method in kinematic data. Muscle coordination was analyzed through EMG linear and non-linear dependencies between signals with coherence (ß/yCOH) and mutual information (ß/yMI) at beta and gamma bands. Fatigue induced joint-specific changes in coordination variability, with wrist rCV decreasing from START to END (39.6 ± 32.9% vs. 21.2 ± 12.4%; p = 0.002), showing a redistribution of coordination demands across the upper limb. At the muscle level, *ßOH increased in selected postural muscle pairs, including brachioradialis-biceps ( p = 0.04), trapezius-biceps ( p = 0.04), and trapezius-brachioradialis ( p = 0.003), while yCOH decreased for trapezius-brachioradialis ( p = 0.01). In addition, ßMI increased for brachioradialis ( p = 0.01) and brachioradialis-biceps ( p = 0.01), while yMI increased within the finger flexors ( p = 0.03). Repeated-measures correlation revealed inverse within-subject associations between wrist rCV and trapezius-brachioradialis yCOH (r rm (10) = -0.57, p = 0.05) and finger*flexor yMI (r rm (10) = -0.61, p = 0.03). These findings are consistent with a multi-level compensatory strategy in which distal joint behavior becomes more constrained while proximal and local muscle coordination is reinforced to sustain suspension under fatigue, offering new insight into joint-muscle coordination during climbing-specific isometric tasks.